2007
DOI: 10.1007/s10067-007-0565-6
|View full text |Cite
|
Sign up to set email alerts
|

Prepatellar Brucella melitensis bursitis: case report and literature review

Abstract: Bursal infection is an uncommon clinical presentation of brucellosis. We herein report a case of Brucella melitensis bursitis that was successfully treated. Other reported cases of brucella bursitis were reviewed. A high degree of suspicion in the right clinical setting is required for the diagnosis of brucella bursitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Previous reviewers have classified the olecranon bursa to be the most common site but our review of the recorded case revealed that prepatellar bursa is more common. This has been probably attributed to local trauma resulting from frequent kneeling among patients handling animals [5]. This patient might have also sustained repeated local trauma/pressure to the elbow as a result of the traditional use of cushion support at sheds by the Bedouin tribes of Arabia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reviewers have classified the olecranon bursa to be the most common site but our review of the recorded case revealed that prepatellar bursa is more common. This has been probably attributed to local trauma resulting from frequent kneeling among patients handling animals [5]. This patient might have also sustained repeated local trauma/pressure to the elbow as a result of the traditional use of cushion support at sheds by the Bedouin tribes of Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Bursitis can be the main manifestation of brucellosis. Fever and local signs of inflammation are absent in the majority of Brucella bursitis [5]. Most of Brucella bursitis patients have symptoms for long period ranging from few months to many years with the exception of few cases presented acutely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lübnan'dan bildirilen bir olguda bir yılı aşkın süredir sol dizde ağrısız şişlik dı-şında sistemik muayene bulgusu olmayan bir olgunun bursa sıvısından alınan örnekte Brucella spp. izole edilmiştir (18). Diğer bir makalede sinüs formasyonu ile birlikte suprapatellar bursitle seyreden bir kronik bruselloz olgusunda da bursit tek bulgu olup, klinik bulguların başlangıcından ancak yedi yıl sonra bursa sıvısından alınan örnekte Brucella bakterisi izole edilmesiyle tanı konulmuştur.…”
Section: İrdelemeunclassified
“…The only descriptive study on human brucellosis was conducted in 1997 on data reported to the epidemiological surveillance unit and showed no sex differences in occurrence, and a seasonal distribution related to the herds' birthing season [12]. Other studies by Lebanese researchers have provided clinical descriptions of brucellosis cases [13][14][15][16][17], while a genetic study highlighted the antimicrobial resistance of Brucella spp. isolates from cultured Lebanese dairy products [18].…”
Section: Introductionmentioning
confidence: 99%